Dissecting Causal Associations of Diet-Derived Circulating Antioxidants with Six Major Mental Disorders: A Mendelian Randomization Study - Hao Zhao; Xue Han; Xuening Zhang; Lingjiang Li; Yanzhi Li; Wanxin Wang; Roger S. McIntyre; Kayla M. Teopiz; Lan Guo; Ciyong Lu (MDPI AG, 2023)
Although observational studies have suggested associations between circulating antioxidants and many mental disorders, causal inferences have not been confirmed. Mendelian randomization (MR) analyses were conducted using summary-level statistics from genome-wide association studies (GWASs) to explore whether genetically determined absolute circulating antioxidants (i.e., ascorbate, retinol, β-carotene, and lycopene) and metabolites (i.e., α- and γ-tocopherol, ascorbate, and retinol) were causally associated with the risk of six major mental disorders, including anxiety disorders (AD), major depressive disorder (MDD), bipolar disorder (BIP), schizophrenia (SCZ), post-traumatic stress disorder (PTSD), and obsessive-compulsive disorder (OCD). MR analyses were performed per specific-outcome databases, including the largest GWAS published to date (from 9725 for OCD to 413,466 for BIP participants), UK Biobank (over 370,000 participants), and FinnGen (over 270,000 participants), followed by meta-analyses. We found no significant evidence that genetically determined diet-derived circulating antioxidants were significantly causally associated with the risk of the six above-mentioned major mental disorders. For absolute antioxidant levels, the odds ratios (ORs) ranged from 0.91 (95% CI, 0.67-1.23) for the effect of β-carotene on OCD to 1.18 (95% CI, 0.90-1.54) for the effect of ascorbate on OCD. Similarly, for antioxidant metabolites, ORs ranged from 0.87 (95% CI, 0.55-1.38) for the effect of ascorbate on MDD to 1.08 (95% CI, 0.88-1.33) for the effect of ascorbate on OCD. Our study does not support significant causal associations of genetically determined diet-derived circulating antioxidants with the risk of major mental disorders.